Dominance of Western Emotional Education on Indigenous Context: The Need for a Culturally Pertinent Emotional Education [Predominancia de la Educación Emocional Occidental en Contexto Indígena: Necesidad de Una Educación Culturalmente Pertinente] - Loncon-Antileo, E (Universidade Estadual de Maringa, 2016)
In this theoretical article we reflect on the challenge of checking the frameworks related to the emotional education that need to recognize and identify the variations of the social and cultural problems associated with the mapuche family education as core of the own emotional formation. We start with a reconsideration of the emotional dimension of the school, accompanied by investigations that aim to the improvement of certain emotional skills in students as well as in professors. This recognition is associated with an ideal of emotional competencies or an emotional ideal in the classroom. Previously, however, in this ideal of emotional education, the emotional knowledge of the student who belongs to the culture of minority groups has not longer been considered, especially when the emotional ideal built on the framework of the family education may be far from the predominant one in the schools. When social and cultural diversity is ignored or misinterpreted in school and in education in indigenous contexts, cultural clashes emerge creating processes of discrimination and inequity. This problem can be addressed with a proper emotional epistemology, allowing for recognition of the emotional education and the mapuche cultural identity by using an intercultural educational approach.